Analis Penggunaan Aplikasi Whatsapp Business dalam Strategi Pemasaran Produk Kunyit dan Temulawak (Kajian Pustaka) - Faiq Rafi’ulhaq; Zain Handoko (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The development of information and communication technology has had a major impact on various aspects of the economy. Now digital communication has become an important part of everyday life, the use of applications such as WhatsApp Business has become an important tool for business people in their marketing strategies. The purpose of this study is to find out how the use of the WhatsApp Business application can increase the effectiveness of marketing strategies. The analysis was carried out using the Literature Review research method from various special journals on the use of the WhatsApp Business application in marketing strategies. The research method used is the Literature Review method from several special journals that contain related topics. Literature search using the Google Scholar database using the keywords WhatsApp Business application and marketing strategy. Articles must be published no later than the last five years. There are 16,600 articles, and the author selects the top 5 articles from the search results and the most relevant articles to the topic. From this study it can be concluded that WhatsApp Business is an effective tool for increasing customer interaction and expanding the reach of a company's marketing. However, to realize the full potential of WhatsApp Business, it is important for entrepreneurs to pay attention to digital communication ethics, present relevant content, and continue to monitor and evaluate their marketing strategies. Further research can be done to investigate the long-term impact of using WhatsApp Business in marketing strategies and the implementation of best practices to maximize its benefits.